Transport Risk Index of Physiologic Stability, Version II (TRIPS-II): A Simple and Practical Neonatal Illness Severity Score - Lee, Shoo K.; Aziz, Khalid; Dunn, Michael; Clarke, Maxine; Kovacs, Lajos; Ojah, Cecil; Ye, Xiang Y.; null (American Journal of Perinatology, 2013)
Objective Derive and validate a practical assessment of infant illness severity at admission to neonatal intensive care units (NICUs).Study Design Prospective study involving 17,075 infants admitted to 15 NICUs in 2006 to 2008. Logistic regression was used to derive a prediction model for mortality comprising four empirically weighted items (temperature, blood pressure, respiratory status, response to noxious stimuli). This Transport Risk Index of Physiologic Stability, version II (TRIPS-II) was then validated for prediction of 7-day and total NICU mortality.Results TRIPS-II discriminated 7-day (receiver operating curve [ROC] area, 0.90) and total NICU mortality (ROC area, 0.87) from survival. Furthermore, there was a direct association between changes in TRIPS-II at 12 and 24 hours and mortality. There was good calibration across the full range of TRIPS-II scores and the gestational age at birth, and addition of TRIPS-II improved performance of prediction models that use gestational age and baseline population risk variables.Conclusion TRIPS-II is a validated benchmarking tool for assessing infant illness severity at admission and for up to 24 hours after.
Keywords: neonates; mortality; risk adjustment; outcomes